2016
DOI: 10.1063/1.4945330
|View full text |Cite
|
Sign up to set email alerts
|

Morphology control of perovskite light-emitting diodes by using amino acid self-assembled monolayers

Abstract: Amino acid self-assembled monolayers are used in the fabrication of light-emitting diodes based on organic-inorganic halide perovskites. The monolayers of amino acids provide modified interfaces by anchoring to the surfaces of ZnO charge-transporting layers using carboxyl groups, leaving the amino groups to facilitate the nucleation of MAPbBr3 perovskite films. This surface-modification strategy, together with chlorobenzene-assisted fast crystallization method, results in good surface coverage and reduced defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 28 publications
0
51
0
4
Order By: Relevance
“…Based on a similar strategy, Wang et al. used an amino‐acid‐based self‐assembled monolayer on top of a ZnO layer, achieving a EQE of 0.43 % and a brightness of 5000 cd m −2 for a MAPbBr 3 ‐based LED . Thus, the usage of an interlayer can boost the performance of the device in three different ways: reduction of the injection barrier, suppression of exciton quenching at the interface, and promotion of the growth of a uniform and pinhole‐free perovskite film.…”
Section: Perovskite‐based Ledsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a similar strategy, Wang et al. used an amino‐acid‐based self‐assembled monolayer on top of a ZnO layer, achieving a EQE of 0.43 % and a brightness of 5000 cd m −2 for a MAPbBr 3 ‐based LED . Thus, the usage of an interlayer can boost the performance of the device in three different ways: reduction of the injection barrier, suppression of exciton quenching at the interface, and promotion of the growth of a uniform and pinhole‐free perovskite film.…”
Section: Perovskite‐based Ledsmentioning
confidence: 99%
“…Based on a similar strategy,W ang et al useda na mino-acid-based selfassembled monolayer on top of aZ nO layer, achievinga EQE of 0.43 %a nd ab rightness of 5000 cd m À2 for a MAPbBr 3 -based LED. [107] Thus,t he usage of an interlayer can boost the performanceo ft he device in three different ways:r eduction of the injection barrier, suppression of exciton quenchinga tt he interface,a nd promotion of the growth of au niform and pinhole-freeperovskite film. Becauseo ft heir low binding energies in perovskites excitons are readily dissociated at room temperature,l eading to quenchingo ft he luminescence.T oe nhance the probability of free-electron and free-hole capture and their subsequent bimolecular radiative recombination, it is therefore required to confine the charge carriersw ithin the emissive layer.…”
Section: Perovskite-based Ledsmentioning
confidence: 99%
“…These works demonstrated that pure perovskites can emit bright EL with very high color purity at RT. Many subsequent studies used a variety of experimental approaches to improve the luminescence efficiencies of PeLEDs (8)(9)(10)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66).…”
Section: Renaissance Of Perovskite Emitters: Bulk Polycrystalline Filmentioning
confidence: 99%
“…3C). PeLEDs without interlayers showed the severe exciton quenching, large charge injection barrier, nonuniform perovskite film coverage, and thus very low EL efficiencies (9,52,61). Use of appropriate interlayers between electrodes and perovskite EMLs can facilitate charge injection by reducing injection barriers (9,49,52,55,61).…”
Section: Renaissance Of Perovskite Emitters: Bulk Polycrystalline Filmentioning
confidence: 99%
See 1 more Smart Citation